Association of Genetic Variations in The PIK3-AKT-mTOR Pathway with Endometriosis Susceptibility: A Preliminary Case-Control Study - Rahele Ghasemian Moghadam; Forough Forghani; Danial Jahantigh; Saeedeh Ghazaey Zidanloo; Mahnaz Rezaei; Mohsen Taheri (International Journal of Fertility and Sterility)
Background: Endometriosis is a complex, heterogeneous disease with several genetic and non-genetic pathogenic factors. The phosphatidylinositol 3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/AKT/mTOR) pathway may influence both progression and different stages of endometriosis. This study aims to investigate the effects of the PIK3CA, AKT1, and mTOR single nucleotide polymorphisms (SNP) with endometriosis risk in an Iranian cohort.Materials and Methods: In this case-control study, samples from 127 patients and 125 controls were examined using allele-specific polymerase chain reaction (AS-PCR) polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP).Results: The PIK3CA rs2230461 and AKT1 rs1130233 had a more than 2.5-fold significant increase in disease risk in a homozygous mutation [95% confidence interval (CI): 1.119 -5.985; 95% CI: 1.093-7.535, respectively]. However, the risk was reduced by half or less than half in carriers of the mutant alleles for mTOR rs2295080 (95% CI: 0.108- 0.927, P=0.036). We confirmed that moderate/severe endometriosis was approximately five times more common in patients with the PIK3CA mutant genotype [odds ratio (OR): 4.800, 95% CI: 2.171-10.611, P<0.001], and over two times more frequent in patients with the AKT1 mutant variant (OR: 2.674, 95% CI: 1.261-5.670, P=0.010). The mutant allele for mTOR rs2295080 was more frequent in patients with stages I and II endometriosis (P=0.022).Conclusion: The results show that PIK3CA rs2230461 and AKT1 rs1130233 SNPs are risk factors for endometriosis and the mTOR rs2295080 gene polymorphism is a protective factor for the development of endometriosis in an Iranian cohort. The PIK3CA rs2230461, AKT1 rs1130233, and mTOR rs2295080 gene polymorphisms should be further investigated as potential candidate SNPs for predicting endometriosis susceptibility.